Numerical Investigation of HSC Columns Retrofitted by CFRP Materials under Combined Load - Mohammed El Youbi; Imad Kadiri; Saïf Ed-Dîn Fertahi; Taoufik Tbatou (Salehan Institute of Higher Education, 2022)
Repairing and retrofitting old civil engineering structures based on reinforced concrete represents a challenge for civil engineering societies all over the world. Environmental impacts such as corrosion and natural disasters like earthquakes can considerably weaken those structures. Reinforced concrete confinement technique using carbon fiber-reinforced polymers (CFRP) is considered as an innovative solution to strengthen the old and damaged structures. In this paper, a numerical simulation was carried out to evaluate the impact of the CFRP jacket as a confining composite material on the compressive strength and the ultimate strain of confined reinforced concrete. A FE model was developed, validated by comparing its results with the available experimental measurements, and finally assessed by performing a parametric study. Indeed, the parametric investigations had as their purpose the evaluation of the level of confinement (different number of plies), namely without plies, one plie, and three plies configuration, that were subjected to different eccentric loading modes e=0, e=25 and e=50 mm, in order to assess the interaction between the combined load that can be represented by compressive and flexural effect. The numerical results were, in fact, in good agreement with the experimental data. In addition, CFRP wrapping had a significant effect on the maximum load of eccentrically loaded columns compared to concentrically loaded columns by increasing the compressive strength with a value of 15% gain compared to the unconfined column. Doi: 10.28991/CEJ-2022-08-04-011 Full Text: PDF